Anaphylaxis in pregnancy: a population‐based multinational European study. (28th May 2020) - McCall, S. J.; Bonnet, M.‐P.; Äyräs, O.; Vandenberghe, G.; Gissler, M.; Zhang, W.‐H.; Van Leeuw, V.; Deneux‐Tharaux, C.; Kurinczuk, J. J.; Knight, M.; ,
Summary: Anaphylaxis in pregnancy is a rare but severe complication for both mother and infant. Population‐based data on anaphylaxis in pregnancy are lacking from mainland European countries. This multinational study presents the incidence, causative agents, management and maternal and infant outcomes of anaphylaxis in pregnancy. This descriptive multinational study used a combination of retrospective (Finnish medical registries) and prospective population‐based studies (UK, France, Belgium and the Netherlands) to identify cases of anaphylaxis. Sixty‐five cases were identified among 4, 446, 120 maternities (1.5 per 100, 000 maternities; 95%CI 1.1–1.9). The incidence did not vary between countries. Approximately three‐quarters of reactions occurred at the time of delivery. The most common causes were antibiotics in 27 women (43%), and anaesthetic agents in 11 women (17%; including neuromuscular blocking drugs, 7), which varied between countries. Anaphylaxis had very poor outcomes for one in seven mothers and one in seven babies; the maternal case fatality rate was 3.2% (95%CI 0.4–11.0) and the neonatal encephalopathy rate was 14.3% (95%CI 4.8–30.3). Across Europe, anaphylaxis related to pregnancy is rare despite having a multitude of causative agents and different antibiotic prophylaxis protocols.